Nutraceuticals for Prenatal, Maternal and Offspring's Nutritional Health - Bhatt, Priyanka; Miraghajani, Maryam Sadat; Pathak, Sarvadaman; Pathak, Yashwant (Boca Raton, FL : CRC Press, 2020)
Although there is an increasing number of pregnant individuals taking nutraceuticals to maintain good health, many gaps exist in the knowledge base. These nutraceuticals might be involved in a wide variety of biological processes, and the biological and epidemiological findings of relevant studies should be examined and analyzed. Nutraceuticals for Prenatal, Maternal and Offspring's Nutritional Health focuses on the role of nutraceuticals for prenatal, mothers, and offspring's health. In recent years, new trends have been established in this area of prenatal nutrition, that is, mother and offspring health based on appropriate nutrition during pre-pregnancy, pregnancy, and after pregnancy. Nutraceuticals and natural products have been used by many cultures and societies around the world. This book focuses on recent trends and potential clinical evaluations of such nutraceuticals and natural products.
OCLC-licensed vendor bibliographic record.
Keywords: Pregnancy -- Nutritional aspects; Functional foods; MEDICAL / Nutrition; MEDICAL / Perinatology & Neonatology; TECHNOLOGY / Food Science